Inflammatory Markers Related to Innate and Adaptive Immunity in Atherosclerosis: Implications for Disease Prediction and Prospective Therapeutics - Hong LZ; Xue Q; Shao H (Dove Medical Press, 2021)
Ling-Zhi Hong,1,* Qi Xue,2,* Hong Shao2 1Emergency Department, Chun’an First People’s Hospital (Zhejiang Provincial People’s Hospital Chun’an Branch), Hangzhou, 311700, Zhejiang Province, People’s Republic of China; 2Department of Cardiology, Zhejiang Provincial People’s Hospital, People’s Hospital of Hangzhou Medical College, Hangzhou, 310014, Zhejiang Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong ShaoDepartment of Cardiology, Zhejiang Provincial People’s Hospital (People’s Hospital of Hangzhou Medical College), No. 158 Shangtang Road, Hangzhou, 310014, Zhejiang Province, People’s Republic of ChinaTel/Fax +86-571-85894283Email shaohong@hmc.edu.cnAbstract: Several lines of evidence have linked a dysregulated inflammatory setting to the pathogenesis of atherosclerosis, which is a form of chronic vascular inflammation. Various inflammatory biomarkers have been associated with inflammation and are recognized as potential tools to monitor the progression of atherosclerosis. A well-studied inflammatory marker in the context of cardiovascular diseases is C-reactive protein (CRP) or, more accurately, highly sensitive-CRP (hs-CRP), which has been established as an inflammatory biomarker for atherosclerotic events. In addition, a growing body of investigations has attempted to disclose the potential of inflammatory cytokines, enzymes, and genetic polymorphisms related to innate and adaptive immunity as biomarkers for predicting the development of atherosclerosis. In this review article, we clarify both traditional and novel inflammatory biomarkers related to components of the innate and adaptive immune system that may mirror the progression or phases of atherosclerotic inflammation/lesions. Furthermore, the contribution of the inflammatory biomarkers in developing potential therapeutics against atherosclerotic treatment will be discussed.Keywords: atherosclerosis, inflammation, immune response, biomarker, hs-CRP